The Earth writes the Great Earthquake and the novel in post-3/11 Japan - Haga, Kōichi 1970- (Ecocritical theory and practice, 2019)
"This book explores how the tremendous earthquake on March 11, 2011 impacted literary authors in Japan and generated issues and perspectives previously unrecognized in Japanese literary and social culture. The disaster itself caused an earthquake, tsunami, and an nuclear accident, and provided the grounds for "post 3/11" literature in Japan"--